Socio- communicative strategies in English and Uzbek newspaper discourse: A comparative study - Rakhmonova , Nafisa Toxir qizi; Tukhtakhodjaeva , Zulfiya Tukhtaevna (The Lingua Spectrum, 2026)
Newspaper discourse plays a crucial role in shaping public opinion and reflecting socio-cultural values within a given society. This study aims to examine the socio-communicative strategies employed in English and Uzbek newspaper discourse from a comparative perspective. Drawing on a qualitative analysis of selected newspaper texts, the research explores how linguistic choices reflect cultural norms, ideological orientations, and communicative intentions in different media environments. The findings reveal that English newspaper discourse tends to prioritize individualism, critical engagement, and pluralism of opinions, whereas Uzbek newspaper discourse emphasizes social stability, collective responsibility, and indirect evaluative strategies. These differences demonstrate the influence of national mentality and cultural traditions on the functional and stylistic features of newspaper communication. The study contributes to cross-cultural media linguistics by highlighting how socio-communicative practices are shaped by broader societal frameworks. Furthermore, the study underscores the importance of incorporating socio-cultural awareness into media discourse analysis and language education. Understanding these differences can enhance learners’ critical media literacy and intercultural competence. Future research may focus on digital media platforms to examine how these socio-communicative patterns evolve in online news environments.